DATABASE OF MIGRATION AND REPLICATION WITH ORACLE GOLDEN GATE - Suharjito, Suharjito; Raymond, Raymond; Ratna, Ida (CommIT (Communication and Information Technology) Journal, 2014)
The main goal of this research is to analyze and design a database configuration of migration and replication in PT Metro Batavia. Research methodologies used in this research are data collecting, analysis and design model. Data collecting method is conducted with library research and direct survey in the company. Analysis method is conducted by analyzing hangar system, migration and reflection process and the available problems. Design method is conducted by designing a prototype for migration process with the implementation of Oracle SQL Developer and replication process with implementation of Oracle Golden Gate. The result of this research is a prototype for configuration of migration and replication process by using Oracle Golden Gate, which can produce two sets of identical data for the purpose of backup and recovery, and also design a simple tool that is expected to help active-active or active-passive replication process. The conclusion of this research is migration process of MySQL database to Oracle database by using Oracle Golden Gate hasn’t been conducted, because Oracle Golden Gate still has bug related to binary log, so database of migration is conducted by using Oracle Golden Gate. However, replication of bi-directional in between database of Oracle by using Oracle SQL Developer can guarantee data availability and reduce work burden from primary database.